2011
DOI: 10.1007/s10548-011-0209-7
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Handedness is not Reflected in Cortical Responses After Basic Nerve Stimulation: A MEG Study

Abstract: Motor dominance is well established, but sensory dominance is much less clear. We therefore studied the cortical evoked magnetic fields using magnetoencephalography (MEG) in a group of 20 healthy right handed subjects in order to examine whether standard electrical stimulation of the median and ulnar nerve demonstrated sensory lateralization. The global field power (GFP) curves, as an indication of cortical activation, did not depict sensory lateralization to the dominant left hemisphere. Comparison of the M20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Simple motor tasks, as in our study, elicit similar responses in both hands, which were also found in our study as well as in other studies with intracranial lesions ( Cheyne et al, 2006 , Nagarajan et al, 2008 , Willemse et al, 2010 ). With respect to the results of sensory stimulation, sensory dominance has not been established with electrical median nerve or pneumatically driven finger stimulation ( Chen et al, 2012 , Zhu et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Simple motor tasks, as in our study, elicit similar responses in both hands, which were also found in our study as well as in other studies with intracranial lesions ( Cheyne et al, 2006 , Nagarajan et al, 2008 , Willemse et al, 2010 ). With respect to the results of sensory stimulation, sensory dominance has not been established with electrical median nerve or pneumatically driven finger stimulation ( Chen et al, 2012 , Zhu et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in sensation have been described in relation to specific occupational groups and function. 28 -30 A recent study by Buitenhuis et al established the use of different sensation standards for normal children. 31 In another study musicians were found to be more sensitive than non-musicians in their dominant hands.…”
Section: Discussionmentioning
confidence: 99%